OPTIMIZING SUPPLY CHAIN MANAGEMENT IN RATTAN FURNITURE MANUFACTURING : A LEAN OPERATIONS APPROACH - Nuriyah Nuriyah; Indro Kirono (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
This study examines the implementation of lean supply chain management to optimize rattan furniture production operations, focusing on key variables such as supply chain inefficiencies (lead time, material waste, raw material fluctuations), lean operations tools (value stream mapping/VSM, just-in-time/JIT, 5S), and performance indicators (KPIs) including lead time, inventory turnover, and defect rates. Using a mixed-methods approach combining qualitative case studies of Indonesian rattan producers with quantitative production data analysis, the research applies VSM, KPI measurements, and descriptive-comparative statistics to identify inefficiencies, analyze lean tool implementation, and propose an operational improvement framework. The results demonstrate that lean implementation (VSM, JIT, 5S) significantly reduces lead time by 29-36% and increases inventory turnover by 61-86%, while also revealing unique findings such as reduction of rattan-specific hidden waste (raw material sorting, non-standard drying) and adaptation of pull systems based on natural material characteristics - proving how lean principles can synergize with local wisdom while addressing skepticism about lean applicability in rattan SMEs